CHAPLAINCY SERVICES: ROLE IN TERTIARY CARE HOSPITAL (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
Rapid modernization and exponential sophistication have taken place over the  last few years in the field of medical sciences. These undoubtedly have  increased longevity and relief from sickness but a lot is desired to be done with  regard to handling care and attention to those who are sick and even to those  who are dead & need to be laid to rest and peace with dignity and respect.  Many people, when they are in the hospital, find that their minds turn quite  naturally to such questions as, "Why is there sickness?" "Why did this happen  to me?" "Am I being punished?" "What is the meaning of life?" These  questions are religious questions. Should such questions come to your mind,  you might find comfort in the words of chaplains.  Excellent and close working relationship with architects, engineer’s project  supervisor and administrative manager could lead to a successful facility and  not the usual hospital atmosphere of fear and dislike so that even the most  reluctant visitors would not mind entering the hospital complex.
Keywords: Chaplain Services; Chaplain; pastoral care; Healing Community; Chaplaincy Management Committee